Impact of working hours on work-life balance - Sarah Holly; Alwine Mohnen (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
To examine the influence of working hours on employees' satisfaction, this article uses a large, representative set of panel data from German households (GSOEP). The results show that high working hours and overtime in general do not lead to decreased satisfaction. Rather, increasing working hours and overtime have positive effects on life and job satisfaction, whereas the desire to reduce working hours has a negative impact on satisfaction. In 2009, nearly 60% of employees wanted to reduce their working hours. The overall number of hours by which employees want to reduce their working time is driven mainly by overtime compensation.
Keywords: J22; J28; J81; M12; 330; satisfaction; overtime; work-life balance; working hours; working time arrangements